Analisis Pengaruh Game Online Dan Motivasi Bermain Terhadap Minat Belajar Siswa SD di Kota Batam - Sama, Hendi; Syahputra, Bayu; Siahaan, Mangapul; Zulkarnain, Zulkarnain; Sabariman, Sabariman; Eryc, Eryc (Journal of Information System and Technology (JOINT), 2025)
This study aims to determine the effect of online games and playing motivation on the learning interest of elementary school students in Batam City. The research method used is a qualitative and quantitative method with variables Online Games (X1), Motivation to Play (X2) and Interest in Learning (Y). The qualitative method took 30 samples of elementary school students, and the quantitative method took 392 samples of elementary school students with the population set at 20,000, because there is no specific number. Qualitative data collection techniques were carried out by interviewing respondents, while quantitative data collection, it was done by distributing questionnaires and measurement using a Likert scale. Data analysis in both methods was carried out using the SPSS application, specifically for the qualitative method was codified first. From the results of the qualitative and quantitative analysis, it can be concluded that the variables Online Games and Motivation to Play partially and simultaneously have a significant effect on the variable Interest in Learning. It can also be concluded that the variable Interest in Learning is influenced by the variables Online Games and Motivation to Play by 59.9% while 40.1% is influenced by other variables not examined in this study.